Solid deformation modeling techniques - Yahya, Syaiful Nizam; Mohd. Suaib, Norhaida; Bade, Abdullah; Shamsuddin, Siti Mariyam (Medwell Publishing, 2006)
Non-rigid solid object deformations techniques have been widely used in the computer graphics community to simulate and animate deformable objects. Both offline and real time applications have already benefited from deformation techniques evolutions. This paper discussed the most popular geometric deformation techniques used for both real time and offline applications such as virtual surgery and motion pictures. Deformations techniques are divided into two sub deformation type which is non-physical based deformations and physical based deformations. Computer Graphics, Physically Based Modeling, Animation and Virtual Reality